Dynamics in blue emitting metal halide perovskites for light emitting diodes - Karlsson, Max (Nanyang Technological University, 2023)
Lighting comprises a large part of the global electricity consumption as of today, and the use of lighting in illumination and displays is only projected to grow. It is therefore imperative to meet this energy demand, not only by means of greener energy production, but also with materials that are both more efficient to fabricate as well as to use. Low cost and energy efficient light sources therefore play an important role in minimizing further greenhouse emissions from the way we choose to live.